Kajian Simbolisme Sego Langgi dalam Tradisi Haul Sunan Sendang - Al Farisi, M. Alan (Javano Islamicus, 2025)
This research is motivated by the author's interest in Sego Langgi, which is the favorite iftar menu of Sunan Sendang during fasting. The author feels that the selection of Sego Langgi as the breaking fast menu must have reasons, meanings, and philosophy. To understand the Sufistic meaning contained in Sego Langgi, the author conducted research titled "The Sufistic Meaning of Sego Langgi in the Haul Process of Mbah Raden Nur Rachmat Sunan Sendang" using qualitative research methods. The data sources in the research were obtained through interviews and documentation or the utilization of existing documents. This research produces a novelty in the realm of Nusantara Sufism scholarship in the form of the Sufi meaning contained in Sego Langgi. Sego Langgi is the favorite iftar menu of Sunan Sendang, rich in values of simplicity and asceticism. Sego Langgi has a Sufi meaning of controlling desires. In Sufism, fasting, which includes breaking the fast and pre-dawn meals, by abstaining from living things, is effective in subduing, controlling, and managing desires.